1993
DOI: 10.1128/jvi.67.1.277-287.1993
|View full text |Cite
|
Sign up to set email alerts
|

Release, uptake, and effects of extracellular human immunodeficiency virus type 1 Tat protein on cell growth and viral transactivation

Abstract: 277 transactivator proteins of human retroviruses may mediate both viral and cellular effects. However, the events associated with the release, the uptake, and the biological effects of extracellular Tat are not yet well understood. In this study, we investigated whether during acute infection of T cells by HIV-1, Tat is released at concentrations sufficient to stimulate HIV-1 gene expression in a paracrine fashion and the events associated with the release of biologically active protein by cells transfected w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
245
0
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 736 publications
(257 citation statements)
references
References 46 publications
7
245
0
1
Order By: Relevance
“…Unlike many other HIV-1 proteins, such as Nef, Vpr and Rev, Tat is actively released by infected lymphocytes (Ensoli et al, 1993) and monocytes (Tardieu et al, 1992). The levels of Tat in the HIV-MCM can accumulate up to 4-7 ng ⁄ mL (present study and Albini et al,Fig.…”
Section: Discussionsupporting
confidence: 52%
“…Unlike many other HIV-1 proteins, such as Nef, Vpr and Rev, Tat is actively released by infected lymphocytes (Ensoli et al, 1993) and monocytes (Tardieu et al, 1992). The levels of Tat in the HIV-MCM can accumulate up to 4-7 ng ⁄ mL (present study and Albini et al,Fig.…”
Section: Discussionsupporting
confidence: 52%
“…Tat is critical for viral replication and it is released by infected cells, including monocytes (21,22) and glial cells (18,20), into the ECM, where it can interact with MMPs. In fact, Tat release is optimal in low serum conditions, such as that provided to the brain by the blood-brain barrier (52), and Tat can also cross the blood-brain barrier bidirectionally (53), so that Tat released in the brain might have effects beyond the brain, or vice versa. Both full-length Tat and Tat 1-72, from the first exon alone, are released (19).…”
Section: Discussionmentioning
confidence: 99%
“…Tat can be secreted from infected or transfected cells, including lymphocytes (11,12), monocytes (13,14), and astrocytes (15), by a leaderless, unconventional pathway (16 -18). However, Tat protein can be taken up by cells from extracellular environment (12,19), which is initiated by the Arg-rich domain binding to anionic cell membrane (20). Studies have shown that Tat can bind to different receptors (including CD26, LRP, and CXCR4; ref.…”
mentioning
confidence: 99%